2002
DOI: 10.1126/science.1072873
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ischemic Brain Damage by Perturbing NMDA Receptor- PSD-95 Protein Interactions

Abstract: N-methyl-D-aspartate receptors (NMDARs) mediate ischemic brain damage but also mediate essential neuronal excitation. To treat stroke without blocking NMDARs, we transduced neurons with peptides that disrupted the interaction of NMDARs with the postsynaptic density protein PSD-95. This procedure dissociated NMDARs from downstream neurotoxic signaling without blocking synaptic activity or calcium influx. The peptides, when applied either before or 1 hour after an insult, protected cultured neurons from excitoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
854
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 901 publications
(900 citation statements)
references
References 20 publications
40
854
3
3
Order By: Relevance
“…Four C-terminal residues of the ligand PDZ2-3 (STVV-COOH) identified in the current study with FRET hybrids are identical to those from the NR1 subunit of NMDA receptor, although Y2H assays have not identified this interaction (40). Finally, short peptides derived from the C terminus of NMDA receptor (NR2) have been shown to prevent neuronal death after stroke in a rat model (41). Using FRET hybrids, several ligands were identified that bound PDZ2 with higher affinity than the peptide derived from NR2, suggesting that this approach could enable discovery of therapeutically useful protein-interaction inhibitors (42).…”
Section: Discussionmentioning
confidence: 92%
“…Four C-terminal residues of the ligand PDZ2-3 (STVV-COOH) identified in the current study with FRET hybrids are identical to those from the NR1 subunit of NMDA receptor, although Y2H assays have not identified this interaction (40). Finally, short peptides derived from the C terminus of NMDA receptor (NR2) have been shown to prevent neuronal death after stroke in a rat model (41). Using FRET hybrids, several ligands were identified that bound PDZ2 with higher affinity than the peptide derived from NR2, suggesting that this approach could enable discovery of therapeutically useful protein-interaction inhibitors (42).…”
Section: Discussionmentioning
confidence: 92%
“…38 Likewise, in rats submitted to focal ischemia, the specific disruption of the interaction between the NR2B subunit of NMDA receptors and the PSD-95, which couples NMDA receptors to neuronal nitric oxid synthase (nNOS), reduced brain damage and improved the neurological function, without the negative consequences associated with blocking NMDA receptors. 39 Thus, dissection of the molecular pathway which couples Ca 2 þ -permeable GluR4-containing AMPA receptors to c-Jun/AP-1 will allow the development of selective therapeutic strategies aiming at the disruption of specific intracellular interactions coupled to glutamate receptors while maintaining the physiological actions of the receptor. Cell culture and transfection HEK293 cells, constitutively expressing the GluR4 flip subunit of AMPA receptors, were cultured in DMEM with 10% heat-inactivated fetal bovine serum (FBS), in the presence of geneticin (G418), and kept at 371C, in a humidified incubator with 5% CO 2 /95% air.…”
Section: Discussionmentioning
confidence: 99%
“…6 B). The loss of NMDA receptor subunit interactions with the postsynaptic scaffold has been shown to block ischemia-induced toxicity (Aarts et al, 2002) but exerts no short term effect on basal synaptic transmission or long-term potentiation formation in hippocampal cultures (Lim et al, 2003). Previous studies have shown that actin depolymerization reduces NMDA channel activity (Rosenmund and Westbrook, 1993).…”
Section: Discussionmentioning
confidence: 99%